The Legend of Archer : Role Playing Game Untuk Anak-Anak Berbasis Mobile - Ilham Hanif Pamulia; Slamet Wiyono; Sharfina Febbi Handayani (P3M Politeknik Negeri Cilacap, 2022)
Game is a part of the entertainment that is made as attractive as possible and can be played using electronic media. The development of games in Indonesia has given rise to a new genre in the form of Role Playing games (RPG) which is currently very popular with children, where players play the role of characters in fictional settings. Currently, there are many games that are played by children, but not many provide knowledge about the hero characters of Indonesian puppet characters. This study aims to develop a mobile-based game about wayang characters, especially Arjuna characters who can train children's ability to solve problems, train creativity and form an unyielding optimistic attitude when completing all levels of The Legend Of Archer Game. This game development method uses stages starting from problem identification, data collection, data analysis, system design, system creation, implementation, and testing.